TINGKAT PENGARUH MOTIVASI KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA TENAGA PENDIDIK DI SMP NEGERI 3 POLEWALI KABUPATEN POLEWALI MANDAR - Pratama, Moch. Givan Andra; Ruslan, Reka; Mappellawa, Andi; Sudirman, Sudirman; Hamri, Hamri (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to: a) determine the influence of work motivation on teacher performance; b) determine the influence of leadership style on teacher performance; and c) determine the influence of work motivation and leadership style on teacher performance. The research location was State Junior High School 3 Polewali in Polewali Mandar Regency, West Sulawesi Province. The population in this study was all 37 teachers. Data analysis methods used were validity tests, reliability tests, partial correlation methods, correlation coefficients, and coefficients of determination. Hypothesis testing was conducted using multiple linear regression methods, including the T-test and F-test. The results of the study indicate that: a) Work motivation does not significantly influence teacher performance at State Junior High School 3 Polewali; b) Leadership style has a positive and significant influence on teacher performance at State Junior High School 3 Polewali; and c) Work motivation and leadership style do not significantly influence teacher performance at State Junior High School 3 Polewali.